1977
DOI: 10.1111/j.1365-2125.1977.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anticoagulant control in patients receiving warfarin.

Abstract: 1A hospital-based drug information system has been used to assess the time for which patients treated with warfarin were outside the range of Thrombotest values 5-10% and 5-15% and to examine possible contributory factors in situations where anticoagulation fell outside these ranges. 2 Anticoagulant control varied with the age of the patient and with concomitant drug therapy but not with patient sex or indication for anticoagulation. 3 Most patients were 'under-anticoagulated' at some stage but patients over 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 9 publications
4
34
0
Order By: Relevance
“…Two studies, 29,30 however, have documented a greater response to anticoagulant treatment with increasing age. In 2 recent retrospective studies 31,32 of patients receiving long-term anticoagulation therapy, there was no association between age and bleeding complications.…”
mentioning
confidence: 99%
“…Two studies, 29,30 however, have documented a greater response to anticoagulant treatment with increasing age. In 2 recent retrospective studies 31,32 of patients receiving long-term anticoagulation therapy, there was no association between age and bleeding complications.…”
mentioning
confidence: 99%
“…Subsequent studies in Dundee showed that the quality of anticoagulant control was rather poor and furthennore that many patients were receiving other drugs known to interact with anticoagulants (O'Malley et al, 1977). This was despite the availability of simple objective measures of the level of control achieved.…”
Section: Uses Ofdrug Epidemiologymentioning
confidence: 92%
“…For some of them, for example age, the direction and the degree with which they interfere with the effects of oral anticoagulants has been determined with some precision (O'Malley et al, 1977;Husted & Andreasen, 1977;Shepherd et al, 1977;Routledge et al, 1979). Other factors such as sex and indication for treatment remain controversial and uncertain (O'Malley et al, 1977;Routledge et al, 1979;Arboix et al, 1984).…”
Section: Discussionmentioning
confidence: 99%